(untitled) (CIPEEX, 2025)
This study examines the procedural effects of the death of the sole attorney of record, focusing on the validity of court notices issued in the deceased counsel’s name before the court is informed. The aim is to set criteria to recognize (or reject) nullity of such acts, reconciling the constitutional centrality of legal counsel with rules on suspension and regularization of representation, and with due process guarantees. The method is a doctrinal and case-law review with normative analysis of the Civil Procedure Code provisions on suspension and counsel replacement, together with the pas de nullité sans grief principle, under which nullity depends on demonstrated prejudice. The findings indicate that notices addressed to a deceased attorney do not fulfill their communicative purpose and are, as a rule, void; however, the sanction hinges on proof of concrete harm and on the absence of timely regularization of representation. Where a new attorney is appointed or valid notice is served directly on the party, validation may occur, provided the rights of defense and adversarial proceedings are preserved. The conclusion is that promptly informing the court of the death and regularizing representation are essential to avoid nullities; when actual prejudice from lack of technical defense is shown, notices issued in the deceased counsel’s name must be deemed null.